Cultura e Interculturalidade em movimento no ensino de Português Língua Estrangeira: um estudo bibliográfico-documental - Yonaha, Tábata Quintana (Universidade Federal de São Carlos, 2021)
This dissertation is the result of a qualitative bibliographic research design. The concepts of culture and interculturality in the Foreign Language Teaching (henceforth FLT) are investigated under the scope of Applied Linguistics. Its main aim was to gather theoretical contributions on these concepts, to relate and discuss them from a critical perspective following an interpretative-constructivist approach. The reference sources for the development of this research were primary (books, articles, technical texts) and tertiary (databases). We present primary concepts about culture in the language studies area (KRAMSCH, 2011; 2017). In addition, we develop a historical overview of the relationship between language and culture based on the works of Risager (1998) and Kramsch (2001; 2006; 2007; 2010; 2011). Another concept presented is culture under different perspectives based on the contributions of Holliday (2012) and Abdallah-Pretceille (2006). This work discusses the most widely used intercultural models in academic research on this theme (BYRAM, 1998; BENNETT, 1998; DEARDORFF, 2009) through analyzing their main characteristics. The in-depth analysis of these models has the emergency of an epistemic turn of popular knowledge and scientific knowledge supported and advocated in Walsh's decolonial proposals (2008; 2010). Issues as power, exclusion, subordination of identities, knowledge, languages and systems are scrutinized in Walsh’s work, as well as in the works of Dervin (2006; 2017). The author problematizes solid conceptions of culture and interculturality while taking the critical interculturality proposals of Tubino (2005) and Candau (2016) into consideration. Seeking, with this discussion, to contribute to the visibility and expansion of this theme in the teaching of Portuguese as a Foreign Language (PFL), we focused on the Celpe-Bras exam due to its washback effects into this field, analyzing guiding documents for the face-to-face interaction of the evaluation process, namely in relation to the notions of culture and interculturality embodied in aspects of the Provocative Elements and Interaction Scripts. We consider that the results of this research can contribute to discussions and, potentially, to the practices of PFL teachers, in initial and in continuous professional development, in a reflexive way, since the pedagogical alternatives presented emphasize the importance of breaking away from solid constructions of culture ( DERVIN; MACHART, 2015) and to question crystallized senses and debatable certainties of knowledge (MOITA LOPES; FABRÍCIO, 2015) about cultures and interculturality in the context of teaching in this area.
Culture and Interculturality on the move in Portuguese as a Foreign Language Teaching: a bibliographic-documentary research
Keywords: Cultura; Interculturalidade; Ensino de línguas; Português língua estrangeira; Celpe-Bras; Culture; Interculturality; Foreign language teaching; Portuguese a foreign language; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA